HUBUNGAN ANTARA DUKUNGAN SOSIAL DAN KEBERMAKNAAN HIDUP PADA PENYANDANG TUNA - Amanda Hayyu; Olievia Prabandini Mulyana (Jurnal Psikologi Teori dan Terapan, 2015)
People with hearing impairment commonly are facing social ninteraction problems, which may affect their life and how they perceived their lifes meaning. Therefore, people with hearing impairment often needs social support to overcome hinders in their life. This research used quantitative research method. The purpose of this research is to test the correlation between social support and lifes meaning on people with hearing impairment in Persatuan Tuna Rungu Indonesia (The Indonesian Union of Hearing Impairment) Surabaya Branch. Social support and lifes meaning scales were given to 50 respondents as research subject, which was using Purposive sampling technique. Data were analyzed using Product Moment Pearson correlation technique. Based on data analysis, it is found that the correlation coefficient is 0,477 with significance value of 0,000 (<0,05). It can be concluded from the result that there is a positive relation between social support and lifes meaning of people with hearing impairments.Abstrak: Penyandang tuna rungu memiliki hambatan dalam melakukan interaksi sosial yang dapat mempengaruhi hidup mereka dan bagaimana mereka memaknai hidup. Oleh karena itu penyandang tuna rungu membutuhkan dukungan sosial untuk mengatasi hambatan yang dihadapi. Penelitian ini menggunakan pendekatan kuantitatif. Tujuan penelitian ini untuk menguji hubungan antara dukungan sosial dengan kebermaknaan hidup pada penyandang tuna rungu di komunitas Persatuan Tuna Rungu Indonesia (Perturi) Surabaya. Skala dukungan sosial dan skala kebermaknaan hidup dibagikan ke 50 orang subjek penelitian yang didapatkan dengan teknik purposive sampling. Teknik analisis data yang digunakan adalah korelasi Product Moment Pearson. Hasil analisis data menunjukkan koefisien korelasi memiliki nilai 0,477 dengan signifikasi sebesar  0,000 (<0,05). Hal ini menunjukkan adanya hubungan positif antara dukungan sosial dan kebermaknaan hidup pada tuna rungu.